Seven letters [large type] - Monninger, Joseph (Thorndike Press large print romance, 2020)
"J. P. Monninger, author of the international bestseller The Map That Leads to You, the novel Nicholas Sparks called "romantic and unforgettable", tells a poignant love story of the ways the world divides two souls--and the way that love brings them together. Kate Moreton is in Ireland on sabbatical from her teaching position at Dartmouth College when she meets Ozzie Ferriter, a fisherman and a veteran of the American war in Afghanistan. The Ferriter family history dates back centuries on the remote Blasket Islands, and Ozzie - a dual citizen of Ireland and the United States - has retreated to the one place that might offer him peace from a war he cannot seem to leave behind. Beside the sea, with Ireland's beauty as a backdrop, the two fall deeply in love and attempt to live on an island of their own making, away from the pressures of the outside world. Ireland writes its own love stories, the legends claim, and the limits of Kate and Ozzie's love and faith in each other will be tested. When his demons lead Ozzie to become reckless with his life--and Kate's--she flees for America rather than watch the man she loves self-destruct. But soon a letter arrives informing Kate that her heroic husband has been lost at sea, and Kate must decide whether it is an act of love to follow him or an act of mercy to forget"--